ARTERIAL HYPERTENSION IN PREGNANCY: MECHANISMS OF FORMATION, PREVENTION AND THERAPEUTIC APPROACHES - A. L. Vertkin; L. E. Murashko; O. N. Tkachova; I. V. Tumbayev (Российский кардиологический журнал)
Arterial hypertension in pregnancy: mechanisms of formation, prevention and therapeutic approaches.